Manfaat Teknologi Ilmu Pendidikan Islam Dunia Maya Dalam Meningkatkan Kualitas Pendidikan Agama Islam - Saqdiatul Khoiriyah (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
The background of this study is the lack of understanding regarding cyber Islamic education technology. To overcome this, Islamic education technology can be used which contains official related internet sites. The formulation of the problem in this study is what are the benefits of cyber Islamic education technology. Therefore, this study is intended to explain the benefits of cyber Islamic education technology. This is a qualitative descriptive research on library research. Based on the research results, it can be concluded that the benefits of cyber Islamic education technology can improve the quality of Islamic religious education.